Performance assessment of an electrostatic filter-diverter stent cerebrovascular protection device. Is it possible not to use anticoagulants in atrial fibrilation elderly patients? - Eguzkitza, Beatriz; Oks, David; Navia, José A.; Houzeaux, Guillaume; Butakoff, Constantine; Fisa, María; Campoy Millán, Ariadna; Vázquez, Mariano (Frontiers in Cardiovascular Medicine, 2023)
strut surfaces, studying the effect of electrical forces on the clots if they are considered charged. Flowrate boundary conditions were used to emulate both healthy and AF patients conditions. When deploying the electronegatively charged device in all three aortic arch arteries, the number of particles entering these arteries was reduced on average by 62.6% and 51.2%, for the healthy and diseased models respectively, and large particles reduced 100% matching or surpassing current oral anticoagulant efficacy. The device demonstrated a two-fold mechanism for filtering emboli: while the smallest particles are deflected by electrostatic repulsion, avoiding microembolisms, which could lead to cognitive impairment, the largest ones are mechanically filtered since they cannot fit in between the struts, effectively blocking the full range of particle sizes analyzed in this study.